MENYIBAK LUKA KEMANUSIAAN DALAM KETIDAKLAYAKAN LEMBAGA PEMASYARAKATAN (LAPAS) - Marianus Ivo Meidinata (Jurnal Ledalero, 2021)
In this study, the author focuses on the reality of the improperness of prison as something that does not suit the values of Pancasila, especially the one which talks about 'just and civilized humanity'. The author would like to explore the motives and causes why the government does not guarantee welfare for the prisoners. This research uses a qualitative approach, with a literature study as a data collection method. The author tries to see the reality of humanity and the motives that underlie the guidance of prisoners through the point of view of phenomenological philosophy. This study concludes that the Indonesian government has not been able to ensure human values for the prisoners. Improperness of the prison such as the overload of occupants is a sign that the perspective of understanding prisons and inmates is still deviant. Prison is not seen as a place of transformation but as a place of punishment, just like the old understanding of prison. The Indonesian people seem to have not been able to regard prisoners as people with dignity. Key words: Humanity, Injustice, Prisoners, Prisons, Pancasila.